PENERAPAN BLENDED LEARNING BERBANTUAN E-WORKSHEET UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII.1 SMP WIDIATMIKA - Payadnya, I Putu Ade Andre; Ni Luh Putu Kartika Wira Lestari (Unika Santu Paulus Ruteng, 2022)
This study was aimed to improve students’ learning achievement in mathematics with the main topic of the lesson was the Two-Variable Linear Equation System through the application of blended learning assisted by e-worksheet. In the implementation of mathematics learning process at this time, it was found that some students felt bored during the learning process and they had difficulty in understanding the material because in the learning process did not use a varied learning method. Through the implementation of blended learning assisted by e-worksheet, students have the freedom to learn the materials by utilizing teaching materials stored online. This research was classroom action based research that was conducted in two cycles. Each cycle consisted of four steps namely planning, action, observation and evaluation, and reflection. Each cycle took three time meetings, where the first and the second meetings were for action and the third meeting was to conduct the final cycle test. The subjects of the study were 25 students from grade VIII.1 of SMP Widiatmika in the odd semester in academic year 2020/2021. The data of students’ achievement in learning mathematics were collected by using multiple choice (objective) test. Based on the results of the study, it showed that there was improvement in each cycle. In the first cycle, the percentage of students completeness in passing the score 65 as Standard of minimum completeness (KKM) of the material was 60% with an average score was 67,76. In the second cycle, the percentage of students completeness in passing the score 65 as Standard of minimum completeness (KKM) of the material was 80% with an average score was 76. The results of the study showed that the implementation of blended learning assisted by e-worksheet ccould improve students’ learning achievement in mathematics.